Pembelajaran Menterjemah Bahasa Indonesia Kedalam Bahasa Inggris Dengan Pemanfaatan Google Translate Mi Billingual Pucang Krian Sidoarjo - Saifulloh, Ahmad Iklil (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The main objective of this program is the implementation of the Artificial Intelligence inklusively Google Translate which can be one of a solution for Teachers who do not study English Language in depth to understand English text as a whole so that it can be a solution in understanding the transition of Indonesian into English. However, teachers at MI Billingual Roudlotul Jannah Sidoarjo must be able to understand both the structure of language and culture in the source language and target language equally so that errors in understanding text can be minimized and can be a solution in understanding English texts. Not only google translate, the use of T-saurus is also an alternative solution to paraphrasing words that are considered rigid from the translation of artificial intelligence google translate.